2008
DOI: 10.1128/jb.02010-07
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Aminopeptidase IV fromStenotrophomonas maltophiliaExhibits Activity against a Substrate Containing a 4-Hydroxyproline Residue

Abstract: The crystal structure of dipeptidyl aminopeptidase IV from Stenotrophomonas maltophilia was determined at 2.8-Å resolution by the multiple isomorphous replacement method, using platinum and selenomethionine derivatives. The crystals belong to space group P4 3 2 1 2, with unit cell parameters a ‫؍‬ b ‫؍‬ 105.9 Å and c ‫؍‬ 161.9 Å. Dipeptidyl aminopeptidase IV is a homodimer, and the subunit structure is composed of two domains, namely, N-terminal ␤-propeller and C-terminal catalytic domains. At the active site,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…4C). DALI searches (23) with the structure of Tsi1 as the bait obtained several structures containing a typical ␤-propeller fold, such as dipeptidyl aminopeptidase IV from Stenotrophomonas maltophilia (Z ϭ 7.2, PDB code 2ECF) (30). Although the structure of Tsi1 can be roughly superimposed with part of the characterized ␤-propeller fold (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4C). DALI searches (23) with the structure of Tsi1 as the bait obtained several structures containing a typical ␤-propeller fold, such as dipeptidyl aminopeptidase IV from Stenotrophomonas maltophilia (Z ϭ 7.2, PDB code 2ECF) (30). Although the structure of Tsi1 can be roughly superimposed with part of the characterized ␤-propeller fold (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stenotrophomonas maltophilia as a template (PDB code 2ECF) 134 and is available from the ModBase database 135 using access numbers 37577089 136 and 123983020 137 for DPP8 and DPP9, respectively. The second set of homology models was reported by Janardhan and Reddy 132 and built using the A chain of a human DPP-IV structure (PDB code 1 × 70) as a template.…”
Section: Comparing the 3d Structures For Dpp-iv Dpp8 And Dpp9mentioning
confidence: 99%
“…Initial phase determination for the PmDAP IV crystal was performed by the molecular-replacement technique using the coordinates of one protomer of SmDAP IV (PDB entry 2ecf; Nakajima et al, 2008), which has approximately 74% aminoacid sequence identity to PmDAP IV, as a search model. Bound water molecules were removed from the search model.…”
Section: Initial Phase Determinationmentioning
confidence: 99%
“…To date, several crystal structures of mammalian DPP IVs have been reported and substrate-recognition mechanisms of the mammalian DPP IVs have been discussed in detail (Engel et al, 2003;Hiramatsu et al, 2003;Rasmussen et al, 2003). However, crystal structure analysis of a bacterial DAP IV has been only reported at medium resolution (2.8 Å ) for DAP IV from S. maltophilia (SmDAP IV; Nakajima et al, 2008) in a peptide-free form. The structural analysis of SmDAP IV revealed that the overall structure of SmDAP IV is similar to those of mammalian DPP IVs; however, an activesite arginine residue (Arg125 in human DPP IV) which is responsible for the recognition of the carbonyl group of the P2 residue of a substrate peptide is not conserved in bacterial DAP IVs.…”
Section: Introductionmentioning
confidence: 99%